Need, speed, and greed : how the new rules of innovation can transform businesses, propel nations to greatness, and tame the world's most wicked problems /: how the new rules of innovation can transform businesses, propel nations to greatness, and tame the world's most wicked problems. (©2012) - Unknown
No abstract available